2023
DOI: 10.1063/5.0170867
|View full text |Cite
|
Sign up to set email alerts
|

Excitons in (Al,Ga)N quantum dots and quantum wells grown on (0001)-oriented AlN templates: Emission diagrams and valence band mixings

Alexandra Ibanez,
Nikita Nikitskiy,
Aly Zaiter
et al.

Abstract: The luminescence efficiency of AlxGa1−xN quantum dots (QDs) and quantum wells (QWs), buried in AlN cladding layers and emitting in the ultraviolet range between 234 and 310 nm, has been investigated. The growth and optical properties have been done using similar aluminum composition (varying from 0.4 to 0.75) for both QDs and QWs. In order to compare as much as possible the optical properties, the QWs were fabricated with a growth time tuned such that the QW width is similar to the average height of the QDs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Such a behavior is universal for (Al,Ga)N-AlN heterostructures and it was previously reported for quantum dots (QDs), but the Stranski-Krastanow growth modes of QDs prevented us from growing low-dimensional systems with aluminum compositions higher than 70-75%. [23] We demonstrate experimentally that neither the shapes of the polarization-resolved PL recorded for edge emission nor the evolution of the full width at half maximum (FWHM) of the PL lines can be interpreted quantitatively in the framework of the k.p description of the band structure of the QWs. This statement also holds concerning the DOP of the light emitted from the edge of the heterostructures.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Such a behavior is universal for (Al,Ga)N-AlN heterostructures and it was previously reported for quantum dots (QDs), but the Stranski-Krastanow growth modes of QDs prevented us from growing low-dimensional systems with aluminum compositions higher than 70-75%. [23] We demonstrate experimentally that neither the shapes of the polarization-resolved PL recorded for edge emission nor the evolution of the full width at half maximum (FWHM) of the PL lines can be interpreted quantitatively in the framework of the k.p description of the band structure of the QWs. This statement also holds concerning the DOP of the light emitted from the edge of the heterostructures.…”
Section: Introductionmentioning
confidence: 88%
“…Based on the in situ reflection high energy electron diffraction measurement, a diagram made of streaky lines was continuously observed that is characteristic of a 2D growth mode. [23] The deposited thickness ranged between 7 and 8 MLs, with one ML corresponding to an average thickness of about 0.256 nm. AFM measurements have also been carried out to characterize the surface morphology of the structures, showing surfaces made of surface monoatomic steps and smooth terraces, with a typical RMS roughness of 0.2 nm and an average terrace width of 70 AE 20 nm and a step height of 1 mL, as indicated in Figure 1c.…”
Section: The Growth and Structural Characterization Of The Samplesmentioning
confidence: 99%
See 3 more Smart Citations